2023
DOI: 10.1002/cta.3543
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated operation of fuzzy‐based TCSC and SMES for low‐frequency oscillation damping in interconnected power systems

Abstract: Modern power networks are enormously complex and frequently interconnected by weak tie-lines, which results in a variety of stability issues such as low frequency oscillations (LFOs). LFOs can have a negative impact on power system stability and tie-line transmission capacity, resulting in catastrophic blackouts if suitable damping control mechanisms are not in situ. This article demonstrates a robust design of damping control for inter-area LFO damping in an interconnected power system. A new comprehensive ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Due to the paucity of space, the numerical results of participation factors with corresponding state names are not shown here but are well documented in Mushtaq and Mufti. 43 5 | DAMPING CONTROL DESIGN…”
Section: System Analysis Using Participation Factor Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the paucity of space, the numerical results of participation factors with corresponding state names are not shown here but are well documented in Mushtaq and Mufti. 43 5 | DAMPING CONTROL DESIGN…”
Section: System Analysis Using Participation Factor Methodsmentioning
confidence: 99%
“…According to the PF investigation, the generators 3 and 4 participate most actively in the interarea oscillations. Due to the paucity of space, the numerical results of participation factors with corresponding state names are not shown here but are well documented in Mushtaq and Mufti 43 …”
Section: Modal Analysismentioning
confidence: 99%
“…Particle swarm optimization was employed by the authors of [23] to develop an output feedback UPFC controller for the damping of electromechanical oscillations. In [24], the authors demonstrated the most effective tuning method for a unified power flow controller to reduce interarea oscillations in a multi-machine system using the firefly method. In [25], the authors described a STATCOM controller design that dampens low-frequency oscillations in the power system using a modified shuffling frog leaping algorithm.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For inter-area LFO damping in interlinked power systems, a robust damping control technique is developed in Mushtaq and Mufti. 18 The technique uses a skillfully created fuzzy logic control system, a thyristor operated series compensator, and superconducting magnetic energy storage. Based on participation factor analysis, a global stabilizing feedback signal is also added.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The fault ride‐through prevention techniques should be applied in the VFT since fault propagation is a key issue that impacts power system security and dependability. For inter‐area LFO damping in interlinked power systems, a robust damping control technique is developed in Mushtaq and Mufti 18 . The technique uses a skillfully created fuzzy logic control system, a thyristor operated series compensator, and superconducting magnetic energy storage.…”
Section: Introductionmentioning
confidence: 99%